Vitamin D receptor polymorphism associated with obesity in productive age population: A cross-sectional study - Yohana; Meiyanti; Hartanti, Monica Dwi; Margo, Eveline; Zuraida, Reni (Faculty of Medicine, Universitas Islam Indonesia, 2025)
Background: Obesity is influenced by genetic factors, lifestyle, and environmental factors. This increase in obesity gives rise to various chronic disease problems.Objectives: This study aimed to identify genetic variations of Vitamin D receptors and determine the relationship to obesity in terms of body mass index and body fat percentage in the working group.Methods: This study is an analytical observational study with a cross-sectional research design approach in the Jembatan Dua area, Angke sub-district, West Jakarta. The research instrument used was a questionnaire to obtain characteristic data, as well as an examination of VDR gene variations rs1544410, rs2228570, rs7975232, and PCR examination to obtain data on gene variation.Results: The results obtained are as follows: the average age of subjects was 42.24, with 58.1% females. A total of 39 (69.1%) are Javanese. Thirty-one (50%) subjects were included in the category of obesity (BMI> 25), and 41 (66.1%) subjects were obese category based on the body fat percentage. The results of bivariate analysis obtained SNP VDR FoxI gene obtained a significant relationship with body mass index with a p-value of 0.047, while the VDR BsmI gene obtained a statistically meaningful relationship with body fat percentage with a p-value of 0.043.Conclusion: FoxI and BsmI VDR polymorphisms are associated with body mass index and body fat percentage.